Current state of concussion prevention strategies: a systematic review and meta-analysis of prospective, controlled studies. Issue 20 (1st June 2016) - Schneider, Daniel K; Grandhi, Ravi K; Bansal, Purnima; Kuntz, George E; Webster, Kate E; Logan, Kelsey; Barber Foss, Kim D; Myer, Gregory D
Abstract : Objective: The aim of the current review was to systematically identify, evaluate and synthesise trials that examine concussion prevention via equipment, educational programmes and training programmes. Data sources: PubMed and EBSCO host (CINAHL, MEDLINE, SPORTDiscus). Eligibility criteria for selecting studies: The electronic databases PubMed and EBSCO were searched using the phrases: concussion prevention equipment, concussion prevention training and concussion prevention education . Included studies utilised a prospective study design to evaluate the preventative effect of: (1) equipment, (2) training or (3) educational programmes on the incidence of concussions in comparison to a control group. Data extraction: Demographic data and intervention methods were recorded. Intervention and control group concussion rates and superficial head injury rates were extracted and combined using random-effects relative risk meta-analysis. Results: 14 studies evaluated interventions of novel protective equipment. One prospective investigation evaluated an educational programme. The relative risk of concussion for participants enrolled in the interventional arms of trials was not significantly different from that in standard practice arms (RR=0.78, 95% CI 0.55 to 1.11, χ 2 =1.8, p=0.17; I 2 =85.3%, 95% CI 71.5% to 90.8%). The relative risk of concussion for participants wearing protective equipment (ie, headgear, full face shields) relative to their counterparts wearing standard or no equipment, calculated from seven available reports, showed no effect of intervention (RR=0.82, 95% CI 0.56 to 1.20, χ 2 =1.06, p=0.30; I 2 =86.7%, 95% CI 73.3% to 91.8%). The relative risk of superficial head injury for participants wearing protective equipment relative to their counterparts, calculated from three reports, showed a significant risk reduction (RR=0.41, 95% CI 0.31 to 0.56, χ 2 =34.13, p<0.0001; I 2 =53.1%, 95% CI 0% to 85.2%). Conclusions: Prospective controlled studies indicate that certain protective equipment may prevent superficial head injury, but these items are suboptimal for concussion prevention in sport.